Long-lived efficient delayed fluorescence organic light-emitting diodes using n-type hosts. Issue 1 (December 2017) - Cui, Lin-Song; Ruan, Shi-Bin; Bencheikh, Fatima; Nagata, Ryo; Zhang, Lei; Inada, Ko; Nakanotani, Hajime; Liao, Liang-Sheng; Adachi, Chihaya
Abstract Organic light-emitting diodes have become a mainstream display technology because of their desirable features. Third-generation electroluminescent devices that emit light through a mechanism called thermally activated delayed fluorescence are currently garnering much attention. However, unsatisfactory device stability is still an unresolved issue in this field. Here we demonstrate that electron-transporting n-type hosts, which typically include an acceptor moiety in their chemical structure, have the intrinsic ability to balance the charge fluxes and broaden the recombination zone in delayed fluorescence organic electroluminescent devices, while at the same time preventing the formation of high-energy excitons. The n-type hosts lengthen the lifetimes of green and blue delayed fluorescence devices by > 30 and 1000 times, respectively. Our results indicate that n-type hosts are suitable to realize stable delayed fluorescence organic electroluminescent devices. OLEDs based on thermally activated delayed fluorescence have shown high fluorescence efficiency but poor lifetime. Herein, Cui et al. demonstrate that the use of n-type host molecules can increase the device lifetime by 30 times and 1000 times for green and blue OLEDs, respectively.